2013
DOI: 10.1017/s175173111200184x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the fatty acid profile of subcutaneous back-fat adipose tissue in growing Iberian and Landrace × Large White pigs

Abstract: The lipid content and fatty acid (FA) profile in pig tissues are strongly influenced by genotype and nutrient supply, with implications in meat quality. The de novo lipid synthesis and pattern of FA unsaturation could be an important cause of variation in the overall efficiency of energy utilization among breeds. To test the effects of pig genotype and CP supply on the evolution of back-fat tissue FA profile throughout the growing and finishing stages, 32 Iberian (IB) and Landrace 3 Large White (LR 3 LW) barro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
30
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 30 publications
7
30
1
Order By: Relevance
“…Moreover LW*GY pigs were six months old at slaughter while IB*D pigs were ten months old, which may possibly be one of the factors that could explain the differences in C18:2 n-6 concentration found in the present trial. However, the daily linoleic intake was in the range from 34.1 to 49.9 g for the LW*GY and from 30.5 to 58.5 g per day for the IB*D pigs, this fact means that the range of total linoleic intake in fresh matter was 1.8 times higher for IB*D than for LW*GY pigs, well above the amounts referenced in previous studies (Serra et al, 1998;Barea et al, 2013).…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Moreover LW*GY pigs were six months old at slaughter while IB*D pigs were ten months old, which may possibly be one of the factors that could explain the differences in C18:2 n-6 concentration found in the present trial. However, the daily linoleic intake was in the range from 34.1 to 49.9 g for the LW*GY and from 30.5 to 58.5 g per day for the IB*D pigs, this fact means that the range of total linoleic intake in fresh matter was 1.8 times higher for IB*D than for LW*GY pigs, well above the amounts referenced in previous studies (Serra et al, 1998;Barea et al, 2013).…”
Section: Discussionmentioning
confidence: 44%
“…In a recent study, Barea et al (2013) showed that lean pigs fed a diet with 17% crude protein presented higher proportions of C18:2 n-6 and PUFA at 38 and 50 kg of body weight in the outer layer than when offered a low protein content diet (13%). In our experiment, we used the same level of crude protein in each genotype.…”
Section: Response Of Different Pig Genotypes To Dietary Linoleic Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…At later stages of growth, our results suggest a genetic variation in the de novo lipid synthesis and pattern of FA unsaturation. Higher desaturase activity in the IB pig, in comparison with a lean pig genotype under the same nutritional regime (Barea et al, 2013) can be associated with lower efficiency of energy utilization for fat deposition found by Nieto et al (2012).…”
Section: Discussionmentioning
confidence: 92%
“…The results of a collaborative study of our research group (Barea et al, 2013) are relevant to the second question. In this study, a comparison was made on the pattern of changes of FA in subcutaneous fat of two pig genotypes which differ profoundly in growth rate and composition of growth: 32 IB and Landrace × Large White barrows were offered one of the two diets differing in CP content (13% or 17% as-fed) throughout the growing and finishing stages of growth.…”
Section: Discussionmentioning
confidence: 99%